1998
DOI: 10.1023/a:1004389031110
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this study a general bead-spring model is used for predicting some rheological properties of a cubic bead-spring structure of arbitrary size immersed in a Newtonian solvent. The topology of this bead-spring structure is based upon the well-known cubic crystals (SC, BCC or FCC) and it consists of equal Hookean springs and beads with equal friction coefficients, while hydrodynamic interaction is not included. An appropriate combination of the equations of motion, the expression for the stress tensor and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Let¯ g and g the sets of nodes generated at iteration g or earlier, respectively. Then S tot (g) can be recast as S tot (g) = i∈¯ g , j∈ g d ij (g)+ i∈¯ g , j∈¯ g d ij (g)+ i∈ g , j∈ g d ij (g), (9) It is evident that the third term on the right-hand side (rhs) of Eq. (9) is exactly S tot (g − 1), i.e.,…”
Section: Average Path Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Let¯ g and g the sets of nodes generated at iteration g or earlier, respectively. Then S tot (g) can be recast as S tot (g) = i∈¯ g , j∈ g d ij (g)+ i∈¯ g , j∈¯ g d ij (g)+ i∈ g , j∈ g d ij (g), (9) It is evident that the third term on the right-hand side (rhs) of Eq. (9) is exactly S tot (g − 1), i.e.,…”
Section: Average Path Lengthmentioning
confidence: 99%
“…Thus far, the Laplacian eigenvalues for some classes of graphs have been determined exactly, including regular hypercubic lattices, 1,9 dual Sierpinski gaskets, 10,11 Vicsek fractals, 12,13 dendrimer also known as Cayley tree, 14 and Husimi cacti. 15,16 Recent empirical research indicated that some real-life networks (e.g., power grid) display small-world behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper 80 we have already shown analytically that the obtained frequency dependency of the dynamic moduli GЈ() and GЉ() belonging to Hookean bead-spring cubes in a Newtonian fluid does not really depend upon the specific cubic topology, i.e., the obtained linear viscoelastic results belonging to the SC, BCC, and FCC cases are essentially the same. We therefore expect that the SC results obtained in this paper shall provide a good qualitative description of the linear viscoelastic behavior of a real colloidal crystal consisting of crystallites of the BCC or FCC type.…”
Section: Introductionmentioning
confidence: 72%
“…͑57͒ and ͑58͒, respectively. By using a standard method 80,85 we obtained for each region asymptotic expressions for the reduced moduli GЈ and GЉ given by Eqs. ͑68͒ and ͑69͒, respectively.…”
Section: Reproducible Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation